2003
DOI: 10.1038/sj.bjc.6600969
|View full text |Cite
|
Sign up to set email alerts
|

DNA copy number changes in young gastric cancer patients with special reference to chromosome 19

Abstract: Only a few cytogenetic and genetic studies have been performed in gastric cancer patients in young age groups. In the present study we used the comparative genomic hybridisation (CGH) method to characterise frequent DNA copy number changes in 22 gastric cancer patients of 45 years or younger and three gastric cancer cell lines established from patients younger than 45 years. Analysis of DNA copy number changes revealed frequent DNA copy number increases at chromosomes 17q (52%), 19q (68%) and 20q (64%). To con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Noteworthy, a previous study using CGH showed gains in the short arm of chromosome 1 in this case (Varis et al, 2003). Chromosome 1 aberrations were also observed in LOH cases.…”
Section: Discussionmentioning
confidence: 91%
“…Noteworthy, a previous study using CGH showed gains in the short arm of chromosome 1 in this case (Varis et al, 2003). Chromosome 1 aberrations were also observed in LOH cases.…”
Section: Discussionmentioning
confidence: 91%
“…Previous CGH studies of gastric cancers yielded similar results. Moreover, several CGH studies identified the 20q region as the most frequent site of gain of DNA in gastric [29][30][31][32]34,35,39 Amplification at 20q has been reported in several cancers, such as colon cancer, 40 pancreatic cancer, 41,42 lung adenocarcinoma, 43 ovarian carcinoma, 44 and osteosarcoma. 45 In our study, gain of 20q was detected in 71 cases (70%) and was associated with the pattern of the cancer-stroma 51 and CYP24 (20q13.2).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, frequent chromosomal alterations, namely, gains on 1p, 6p, 7q, 8q, 11q, 16p, 17q, 20q, and 22q, and deletions on 3p, 4q, 5q, 9p, 16q, 17p, 18q, and 19p were observed in gastric cancer. [28][29][30][31][32][33][34][35] Recently, microarray technologies have emerged as key tools for the expression analysis of gene and genes expressed in gastric cancers have been examined using cDNA microarray technique. 36 In the present study, to identify regions of the genome that might be involved in the oncogenesis of gastric cancers, we made an extensive study of chromosomal alterations in such cancers by CGH.…”
mentioning
confidence: 99%
“…They concluded that these differences in genomic profiles likely reflect different pathogenic mechanisms of the disease. Varis et al, similarly observed that the most frequent cytogenetic aberrations were gains seen at 17q, 19q, and 20q in younger patients (Varis et al, 2003). They also found that DNA copy number changes were mostly detected in intestinal or mixed types of tumours.…”
Section: Chromosomal Instability (Cin) and Aneuploidymentioning
confidence: 64%